Nao Tan Qing ameliorates Alzheimer's disease-like pathology by regulating glycolipid metabolism and neuroinflammation: A network pharmacology analysis and biological validation. (November 2022) - Li, Qianqian; Jia, Caixia; Wu, Hongxing; Liao, Yajin; Yang, Ke; Li, Shuoshuo; Zhang, Jing; Wang, Jinlei; Li, Guo; Guan, Fangxia; Leung, Elaine; Yuan, Zengqiang; et al.
Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive decline and currently there are no available treatments. Alongside the conventional Aβ and tau hypotheses, neuroinflammation and metabolism disruption have also been regarded as crucial hallmarks of AD. In this study, a novel Chinese formula Nao Tan Qing (NTQ) was developed and shown to improve AD. In vivo experiments showed that NTQ significantly mitigated cognitive impairment, Aβ burden and neuroinflammation in a transgenic AD mouse model (5×FAD). Network pharmacology results revealed that the active components of NTQ could target inflammatory and metabolic pathways. In addition, hippocampal transcriptomics suggested that NTQ regulated signaling pathways related to inflammation and lipid metabolism. Consistently, serum metabolomics further indicated that NTQ could modulate glycolipid metabolism. In summary, a combination of systems pharmacology analysis and biological validation study demonstrates that NTQ could alleviate behavioral abnormality and pathological alterations of AD by targeting glycolipid metabolism and neuroinflammation, and is accordingly a potential therapeutic agent for AD. Graphical Abstract: ga1